2015
DOI: 10.1080/23294515.2015.1058303
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of therapeutic misconception among incarcerated clinical trial participants

Abstract: Background Therapeutic misconception, the misunderstanding of differences between research and clinical care, is widely prevalent among non-incarcerated trial participants. Yet little attention has been paid to its presence among individuals who participate in research while incarcerated. Methods This study examined the extent to which seventy-two incarcerated individuals may experience therapeutic misconception about their participation in one of six clinical trials, and its correlation with participant cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…These results illustrate a general ethical research challenge, namely participants' difficulties in understanding the nature of clinical trials, including the distinction between treatment in general and research participation. The term "therapeutic misconception" means that a research participant does not fully understand that the primary purpose of a trial is to produce knowledge for the benefit of future patients, as distinct from helping the patient with her current condition (30,(36)(37)(38)(39). These misconceptions might result in unrealistic expectations, and thus disappointment at the lack of help offered during the encounters with the data collectors.…”
Section: The Participantsmentioning
confidence: 99%
“…These results illustrate a general ethical research challenge, namely participants' difficulties in understanding the nature of clinical trials, including the distinction between treatment in general and research participation. The term "therapeutic misconception" means that a research participant does not fully understand that the primary purpose of a trial is to produce knowledge for the benefit of future patients, as distinct from helping the patient with her current condition (30,(36)(37)(38)(39). These misconceptions might result in unrealistic expectations, and thus disappointment at the lack of help offered during the encounters with the data collectors.…”
Section: The Participantsmentioning
confidence: 99%
“…12 Many studies have shown that the prevalence of therapeutic misconception is high among research participants. 13,14 Analysis of consent forms of Phase 1 gene transfer trials by Kimmelman et al, showed that the forms have been designed blurring the distinction between research and patient care. 15 Thus, the ICMR ethical guidelines mandate the inclusion of the term "research", and word the PIS in an unambiguous manner to prevent this possibility of therapeutic misconception.…”
Section: Discussionmentioning
confidence: 99%
“…12 These findings were consistent with other studies that documented TM in over half of trial participants in clinical research. [14][15][16][17] Although it is clear that TM poses a threat to valid consent, an emerging body of literature has questioned whether the reported prevalence of TM among research participants is actually overestimated as a result of discrepancies between patient and research interviewer interpretation of TM questions. 13,[18][19][20] These studies suggest that patients interpreting a question differently than intended by the interviewer introduces a measurement error.…”
Section: Introductionmentioning
confidence: 99%